The Living And The Dead - Osofisan, Sola (Heinemann Educational Books Nigeria, 1991)
This book is a collection of five captivating stories.The stories are woven round the contemporary issues of our society.
Keywords: Fiction; General; Fiction; Mystery & Detective; Traditional British; Nigerian Fiction (English)